Does Anatomic Phenotype of Mitral Annular Disjunction Impact Survival? An Autopsy-Based Retrospective Study - Nan Zhou; Qianhao Zhao; Rui Li; Da Zheng; Yuxi Xiao; Danmi Mao; Yunyi Wang; Jiacheng Yue; Kai Zhang; Jonathan C. Makielski; Jianding Cheng (Journal of Cardiovascular Development and Disease, 2021)
Controversies have been raised regarding the prevalence and potential clinical significance of mitral annular disjunction (MAD). We aim to address the anatomic characteristics of MAD and their association, if any, on survival. We retrospectively reviewed 1373 consecutive dissected hearts (1017 men, mean age at death 44.9 ± 0.4 y) and frequently detected MAD (median disjunctional length: 2.0 mm, range: 1.5 mm~8.5 mm), with the prevalence of 92.1% over the entire mitral annulus and 74.9% within the posterior annulus (pMAD). The presence of pMAD was associated with increased all-cause mortality (45 y vs. 49 y, hazard ratio [HR]: 1.28, 95% confidence interval [CI]: 1.11~1.47, p < 0.001), which persisted in the context of cardiovascular diseases (CVDs; 46 y vs. 51 y, HR: 1.33, 95% CI: 1.14~1.56, p < 0.001) but was insignificant in those without CVDs. Compared to those without pMAD, individuals with pMAD affecting the entire posterior annulus or having a mean standardized length of ≥1.78 showed other clinically significant cardiovascular phenotypes, including the enlargement of aortic annular circumferences and a higher occurrence of thoracic aortic aneurysm/dissection. This largest series of autopsies show that MAD is a common phenotype that may exert additive influence on the survival of individuals. It is necessary to establish a precise classification and stratification of MAD.